2020
DOI: 10.1016/j.jaci.2020.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Addendum Guidelines for Peanut Allergy Prevention by US allergists, a survey conducted by the NIAID, in collaboration with the AAAAI

Abstract: Background: In 2017, the Addendum Guidelines for the Prevention of Peanut Allergy were published with recommendations on early introduction of peanut-containing foods based on infants' clinical history. Objective: We sought to conduct a nationwide US survey to assess Guidelines implementation among allergists and immunologists who manage infants for food allergy. Methods: Survey invitations were delivered to 3281 nonretired, US members of the American Academy of Asthma, Allergy & Immunology, board certified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…51,68 Implementation of the guidelines for food allergy prevention has been challenging. [70][71][72] Although peanut introduction in the first year of life in Australia increased from 28.4% to 88.6%, the rates of peanut allergy did not significantly reduce (3.1% in 2007-2011 vs. 2.6% 2018-2019, p = 0.26). The paper did not report on the duration or frequency of peanut intake, or the way in which peanut was introduced (e.g., boiled, roasted, in a matrix), only timing of peanut introduction.…”
Section: An Oun Ce Of Pre Venti On Is Worth a P Ound Of Curementioning
confidence: 94%
See 1 more Smart Citation
“…51,68 Implementation of the guidelines for food allergy prevention has been challenging. [70][71][72] Although peanut introduction in the first year of life in Australia increased from 28.4% to 88.6%, the rates of peanut allergy did not significantly reduce (3.1% in 2007-2011 vs. 2.6% 2018-2019, p = 0.26). The paper did not report on the duration or frequency of peanut intake, or the way in which peanut was introduced (e.g., boiled, roasted, in a matrix), only timing of peanut introduction.…”
Section: An Oun Ce Of Pre Venti On Is Worth a P Ound Of Curementioning
confidence: 94%
“…Implementation of the guidelines for food allergy prevention has been challenging 70–72 . Although peanut introduction in the first year of life in Australia increased from 28.4% to 88.6%, the rates of peanut allergy did not significantly reduce (3.1% in 2007–2011 vs. 2.6% 2018–2019, p = 0.26).…”
Section: An Ounce Of Prevention Is Worth a Pound Of Curementioning
confidence: 99%
“…Although early introduction of peanut has increased since 2015, there continues to be variation in implementation of these guidelines [16 ▪ ,17,18 ▪ ]. Reasons for this include provider lack of knowledge or comfort, parental concerns, lack of clear guidance on risk stratification, and inconsistent recommendations across various guideline documents [19,20 ▪▪ ,21,22 ▪ ,23 ▪ ]. Furthermore, the use of allergy testing in both high-risk and low-risk infants has increased as these guidelines were introduced, which can inadvertently delay peanut introduction [24].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Other clinical trials have been conducted, but when it comes to widespread implementation of a novel guideline, other studies have not had the capacity to study prevalence, but have rather utilized surveys to assess guideline awareness and implementation. For example, in 2018, Johnson et al administered a cross-sectional survey to 825 allergists in the US to assess their awareness and implementation of the 2017 National Institute of Allergy and Infectious Diseases (NIAID) Addendum Guidelines for the Prevention of Peanut Allergy. The survey found that nearly all allergists (97.1%) were aware of the guidelines and 64.5% reported full and 34.4% reported partial implementation.…”
mentioning
confidence: 99%